Capabilities, gender, equality : towards fundamental entitlements - Comim, Flavio; Nussbaum, Martha Craven, 1947- (Cambridge : Cambridge University Press, 2014)
Questions of gender, injustice and equality pervade all our lives, and as such, the capabilities or 'human development' approach to understanding well-being and basic political entitlements continues to be debated. In this thought-provoking book, a range of authors provide unique reflections on the capabilities approach and, specifically, Martha C. Nussbaum's contributions to issues of gender, equality and political liberalism. Moreover, the authors tackle a broad range of development issues, including those of religion, ecological and environmental justice, social justice, child care, disability and poverty. This is the first book to examine Nussbaum's work in political philosophy in such depth, bringing together a group of distinguished experts with diverse disciplinary perspectives. It also features a unique contribution from Nussbaum herself, in which she offers reactions to the discussion and her latest thoughts on the capabilities approach. Capabilities, Gender, Equality will interest a wide range of readers and policy-makers interested in new human development policies.
10. The Capabilities Of Women: Towards An Alternative Framework For Development / Muriel Gilardone / Isabelle Guérin / Jane Palier -- 11. Applying The Capabilities Approach To Disability, Poverty, And Gender / Santosh Mehrotra -- 12. Educational Transformation, Gender Justice And Nussbaum's Capabilities / Patricia Welch Saleeby -- 13. The Social Contract, Unpaid Child Care And Women's Income Capability / Melanie Walker -- 14. Lists And Thresholds: Comparing The Doyal-Gough Theory Of Human Need With Nussbaum's Capabilities Approach / Hilde Bojer -- 15. Nussbaum, Rawls, And The Ecological Limits Of Justice: Using Capability Ceilings To Resolve Capability Conflicts / Ian Gough -- 16. Social Justice And Nussbaum's Concept Of The Person / Breena Holland -- 17. God And Martha C. Nussbaum: Towards A Reformed Christian View Of Capabilities / John M. Alexander.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Economic development -- Developing countries; Equality -- Developing countries; Social planning -- Developing countries